The process of teaching anti-financial fraud and individual risk management in a non-economic university - Denis S. Krylov; Inna S. Lebedeva (Russian Journal of Education and Psychology)
Background. Among the key trends of the modern economy are digitalization, the growth in the number of users of banking services, and the activity of citizens in the financial market. The growth of the key rate, attractive deposit conditions, and the ease of starting investment activities through mobile applications contribute to the development of this segment. This trend is also understood by those who want to earn money illegally and, as a result, the growth in the number of cases of financial fraud. In these conditions, it is necessary not only to improve financial literacy and learn how to improve your well-being, but also to learn how to combat financial fraud and interact with law enforcement agencies.